Colloidal Metal Surfaces as Biosensors of Biological Samples - Tąta, Agnieszka; Gralec, Barbara; Proniewicz, Edyta (Journal of Casting & Materials Engineering, 2017)
Colloidal solutions of silver (AgNPs), gold (AuNPs), and platinum nanoparticles (PtNps) obtained under controlled conditions in an aqueous media by chemical methods were used as effective biosensors of biological compounds such as bombesins (BN). The BN adsorption at the metal/aqueous interface was investigated by surface-enhanced Raman scattering (SERS). Briefly, the spectral pattern of BN in the silver, gold, and platinum sols is strongly influenced by the indole ring vibrations of L-tryptophan at position 8 of the amino acid sequence (Trp8). In addition, L-methionine (Met) at the C-terminus determines the BN adsorption, mainly onto the AuNPs and AgNPs surfaces.